Expression of P-selectin, TXA2, TGF-β1 and PDGF-AB in the Presence of Bioadhesive Chitosan Derivatives - Periayah, Mercy Halleluyah; Halim , Ahmad Sukari; Yaacob, Nik Soriani; Mat Saad, Arman Zaharil; Hussein, Abdul Rahim; Abdul Rashid, Ahmad Hazri (Online Research Book Publication, India, 2014)
Chitosan is a natural macromolecular polysaccharide, derived from chitin extracted from the exoskeleton of some marine invertebrates. This study was designed to evaluate the expression of P-selectin, thromboxane A2 (TXA2), transforming growth factor-β1 (TGF- β1) and platelet derived growth factor-AB (PDGF-AB) using enzyme-linked immunosorbent assays (ELISAs). The chitosan derivatives utilized were 7% N,Ocarboxymethylchitosan (NO-CMC) (with 0.45 mL collagen), 8% NO-CMC, oligo - chitosan (O-C) and oligo -chitosan 53 (O-C 53). We found that O-C showed a significantly superior effect compared to NO-CMC in achieving hemostasis. Post-hoc multiple comparisons using Scheffe test indicated that p-values between the mean differences of all the assayed chitosan derivatives were not significant. However, our analyses successfully identified distinctions between the O-C and NO-CMC test groups and blood alone. These results may expand the understanding of the ability of chitosan derivatives to promote inflammatory responses and angiogenesis depending on their physical and chemical structures